PENINGKATAN PROFITABILITAS USAHA MELALUI PRODUCT BRANDING DAN DIVERSIFIKASI OLAHAN PISANG KEPOK BAGI PKK KALURAHAN SEMANU GUNUNG KIDUL - Handayani, Titin Hera Widi; Sulasmi, Sulasmi; Baroroh, Kiromim; Kusuma, Chusnu Syarifah Diah; Kusumawardani, Nita (LPPM Universitas Flores, 2024)
This community service aims to increase the business profitability of PKK members in the Semanu sub-district, Gunung Kidul, through product branding training and diversification of kepok banana preparations. Banana kepok, abundant in the region, has economic potential that has not been optimally utilised. The programme was implemented through a series of training and mentoring involving 30 PKK members. The methods used included lectures, hands-on practice, and consultation. The training materials included processing techniques for pisang kepok into various value-added products, branding strategies, and product marketing. The results showed an increase in participants' knowledge and skills. Participants successfully developed four variants of processed kepok banana products with attractive packaging and branding. The community service activities focused on increasing business profitability through product branding strategies and diversification of processed kepok bananas for PKK Semanu Village have shown positive results. Based on a survey, most participants felt an increase in skills in processing products and gained new insights related to branding and marketing. As a follow-up step, regular mentoring is provided to the participants to ensure that the skills and knowledge gained during the training can be optimally applied in the business. Recommendations for programme sustainability include continued mentoring and expansion of marketing networks.